Optimizing Local Human Resources through Entrepreneurship and Economic Education to Improve MSME Performance in Semanding Village, Tuban: Optimalisasi Potensi SDM Lokal Melalui Kewirausahaan dan Pendidikan Ekonomi dalam Meningkatkan Kinerja UMKM di Desa Semanding, Tuban - Yuanis, Yuanis; Sukistanto, Sukistanto; Ndruru, Seputri (Indonesian Journal of Cultural and Community Development, 2025)
This community service activity aimed to enhance the capacity of local human resources at UD Sekar Pratiwi, a home industry in Semanding Village, Tuban. The business employed eight local workers with limited educational backgrounds and no previous experience. Through training and mentoring, the program focused on financial literacy, simple bookkeeping using spreadsheets, digitizing product records, and promoting the use of social media (Instagram, TikTok, Facebook, and WhatsApp) for product marketing. As a result, participants showed improved skills in financial documentation and digital marketing, and the business began expanding its market reach online. Highlights: Capacity Building: Training improved financial and marketing skills of local workers. Digital Adoption: Business began using social media for broader online reach. Skill Uplift: Participants gained practical knowledge despite limited formal education. Keywords: MSMEs, financial literacy, digital marketing, community empowerment, Semanding